2014
DOI: 10.1371/journal.pntd.0003094
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis in Rio de Janeiro, Brazil: Sporothrix brasiliensis Is Associated with Atypical Clinical Presentations

Abstract: BackgroundThere have been several recent changes in the taxonomy of Sporothrix schenckii as well as new observations regarding the clinical aspects of sporotrichosis. In this study, we determined the identification of the Sporothrix species associated with both classic and unusual clinical aspects of sporotrichosis observed in the endemic area of sporotrichosis in Rio de Janeiro, Brazil.Methodology/Principal FindingsTo verify whether S. brasiliensis is associated with clinical manifestations of sporotrichosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
174
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(189 citation statements)
references
References 34 publications
7
174
1
7
Order By: Relevance
“…35 Moreover, S. brasiliensis is associated with zoonotic transmission and atypical clinical presentations in humans. [36][37][38] However, the isolates of S. brasiliensis from Rio Grande do Sul differ molecularly of those from Rio de Janeiro, São Paulo and Minas Gerais, 1,12 which deserves more investigation.…”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, S. brasiliensis is associated with zoonotic transmission and atypical clinical presentations in humans. [36][37][38] However, the isolates of S. brasiliensis from Rio Grande do Sul differ molecularly of those from Rio de Janeiro, São Paulo and Minas Gerais, 1,12 which deserves more investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients infected with S. brasiliensis respond well to these drugs (Francesconi et al 2011, Almeida-Paes et al 2014, Macedo et al 2015), although therapeutic failures have been reported (Almeida-Paes et al 2016). In order to guide therapy, antifungal susceptibility tests were developed (CLSI 2008).…”
mentioning
confidence: 99%
“…Sporotrichosis is considered a rare disease in dogs, with isolated cases in the literature [18]. However, an increasing number of cases have been reported in Rio de Janeiro, associated with an epidemic outbreak in cats, from 1998 to 2009 [2,6,20]. In the present report, contact with cats was deemed an important risk factor, detected in the anamnesis, which allowed the inclusion of sporotrichosis as a differential diagnosis for the presented lesions.…”
Section: Discussionmentioning
confidence: 60%